2005
DOI: 10.1016/j.ejcnurse.2004.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for Cardiac Surgery—Support Experienced by Next of Kin

Abstract: Background: Next of kin (NoK) play a crucial role for patients waiting for cardiac surgery. Aim: To describe experience of support, in the form of important events, by next of kin while their intimates were waiting for a heart operation. Methods: The design was qualitative and the “critical incident” technique was used. Incidents were collected via interviews with 23 next of kin to patients waiting for heart surgery and the informants were chosen by the patient themselves. Findings: In all, 224 important ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
(52 reference statements)
2
17
0
Order By: Relevance
“…The Edwards study also showed that the leaflets were read by the patients and their next of kin about five times before the surgery. The next of kin play a crucial role for patients waiting for cardiac surgery, and it has been shown that they experience support when they receive information and attention, and are involved in the care [18].…”
Section: Discussionmentioning
confidence: 99%
“…The Edwards study also showed that the leaflets were read by the patients and their next of kin about five times before the surgery. The next of kin play a crucial role for patients waiting for cardiac surgery, and it has been shown that they experience support when they receive information and attention, and are involved in the care [18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as a patient with cardiac disease receives care from several different health care providers, the information given to the patient is often varied and not well synchronized [5]. Patients and their next of kin often notice that health care providers believe that information-giving is the responsibility of another care giver, with no one taking full responsibility to ensure that patients and their next of kin are given the information they really need [6,7]. Well-informed patients are likely to be more satisfied with the care and information and this has been found to alleviate anxiety and fear in cardiac patients [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In order to facilitate data collection, a semistructured interview guide was developed (Table 2) based on previous research (Ivarsson et al, 2005, Ivarsson et al, 2011 and a review of the literature. One pilot interview (not included in the study according to the informant's wishes) was conducted to evaluate whether events were verified satisfactorily in response to the questions.…”
Section: Data Collectionmentioning
confidence: 99%